FUN LEARNING WITH COMPUTER BAGI SISWA TK KRISTEN 1 SATYA WACANA SALATIGA - Hermawan, Anton; Nataliani, Yessica; Dwi Purnomo, Hindriyanto; Christianto, Erwien; Setyanti, Angela Atik; Yulia, Hanita; Krismiyati, Krismiyati; Juliastomo Gundo, Adriyanto; Bayangkariwati Tacoh, Yuliana Tien; Wellem, Theophilus; Hendry, Hendry; Chandra, Dian W. (Midang, 2025)
ABSTRACT. The rapid development of information technology necessitates adjustments across various sectors, including education, particularly in early childhood education. Introducing technology at an early age is considered a strategic step in preparing children to face the challenges of the digital era. This community service program aimed to introduce technology, specifically computers, to kindergarten students. The program was in-person for students aged 4 to 5 years at TK Kristen 1 Satya Wacana, Salatiga. The training was conducted over multiple sessions, starting with an introduction to computer hardware, then developing mouse-handling skills, and engaging in interactive learning activities through educational games that addressed subjects like letters, numbers, geometric shapes, and different types of vehicles. Evaluation results revealed that the participants showed high enthusiasm throughout the sessions. The students also began to recognize computers as an alternative learning medium and other digital devices commonly used at home, such as smartphones and tablets. These findings suggest that a digital game-based learning approach can effectively enhance both students’ learning motivation and basic computer operation skills at an early age. Keywords: childhood education, computer training, education game, fun learning, gamebased learning.